Peranan Lembaga Pemasyarakatan dalam Memberikan Pembinaan terhadap Narapidana - Heldiora Silva Simamora; Janpatar Simamora (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
A correctional institution is the final institution for the implementation of criminal justice which provides guidance to people who have committed a crime with the aim of changing the bad behavior of prisoners so that they can be accepted again in the midst of society outside and trying to protect prisoners from committing crimes again. In carrying out rehabilitation for criminals who are in prison, prisoners will have their rights fulfilled in accordance with the law that regulates them. Apart from that, they also have obligations that must be carried out while carrying out their prison term. However, there are many obstacles that make the process of coaching criminals less than optimal in its implementation, for example the lack of officers and experts, obstacles to infrastructure, and obstacles from the community and obstacles that come from the prisoners themselves who often put up resistance to the guard officers. So it is still often found that prisoners repeat crimes again because correctional institutions are not optimal in providing guidance.